The Effectiveness of Simulation Training in an Advanced Trauma Life Support Program for General Surgery Residents: A Pilot Study - Myoung Jun Kim; Jae Gil Lee; Seung Hwan Lee (Journal of Trauma and Injury)
Purpose Although the Advanced Trauma Life Support (ATLS) course is now taught internationally, it has not been implemented in Korea. In recent years, interest has increased in simulation as a teaching tool in the ATLS course. We therefore hypothesized that simulation training would be a useful adjunct to the ATLS course. Methods We designed a 1-day curriculum that included skill development workstations, expert lectures, trauma patient simulations, and group discussion for general surgery residents. We conducted a survey to evaluate participants’ level of understanding of the initial evaluation and treatment of trauma patients, their degree of knowledge and technical improvement, their satisfaction with the learning goals, and their overall satisfaction with the curriculum. We then analyzed the effects before and after the training. Results Nine residents attended this course. None of the residents initially reported that they could perform a primary survey of trauma patients. The analysis revealed significant improvements after training in the questionnaire areas of “assembly of the team and preparation for resuscitation of a trauma patient” (p=0.008), “performance of a primary survey for trauma patients” (p=0.007), “resuscitative procedures for trauma patients” (p=0.008), “importance of re-evaluation” (p=0.007), “identifying the pitfalls associated with the initial assessment and management” (p=0.007), and “importance of teamwork” (p=0.007). Conclusions After the ATLS simulation training, all participants showed significant improvements in their understanding of how to manage multiple trauma patients. Therefore, ATLS simulation training for residents will help in the management of trauma patients.